Diagnosis and Management of Drug-Induced Liver Injury After the Use of Polygonum multiflorum. Issue 10 (12th October 2022) - Zahir, Ali; Li, Michael; Gill, Ryan M.; Brandman, Danielle
ABSTRACT: Polygonum multiflorum, a species of flowering plant in the buckwheat family, is widely used in alternative medicine. However, a growing body of literature has implicated P. multiflorum as a cause of drug-induced liver injury. We report a case of successful treatment of a drug-induced liver injury after consumption of an herbal tea containing P. multiflorum .